PENERAPAN PEMBELAJARAN IPA DENGAN METODE PROYEK DI LINGKUNGAN SEKOLAH DASAR - Reffiane, Fine (MALIH PEDDAS, 2013)
True human nature is friendly and close to nature, but due to the development of more advanced civilization brought journey of human life to be biased. So many people who seemed to lose its identity as a part of nature. The problem is when we want to know and understand nature through a learning process in schools will find obstacles result from the difficulty we bring children closer to nature. We as teachers so find it difficult to plan the learning program in order to bring children closer to nature. The problem is when we are at the level of the program, many of the procedures that we have to pass that we forget the essence of science education is closer to the students closer to nature. For the primary level, learning approach with perspective students closer to nature can be reached through a variety of approaches and methods such as CTL approach, inquiry, Explorative and others. In essence these ideas are closer pitched at students as learners with learning resources more concrete, concrete approach (manipulation) or until the concrete as concrete-concrete, with a note at all possible. The sense is closer to students with learning resources do not always have to bring concrete objects or bring students into the atmosphere of concrete. In certain circumstances we may not bring students to the moon to study the moon and bring elephants into the classroom to introduce students to the elephant but we manipulate it in the form of images.